ANALISIS DISPOSISI MATEMATIS MAHASISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CORE (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) - Rifka Agustianti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of the research is to analyze the mathematical disposition of first level students. The research population is all 1st grade students at one of the Private Universities in Bandung. In this study, two sample classes were taken, one class as the control class and the other as the experimental class. The research design used is Posttest-Only Control Design. A set of mathematical disposition scales consisting of positive statements and negative statements using a Likert scale to determine students' mathematical dispositions is used as an instrument in this study. The data analysis technique used is descriptive statistics. After the data analysis process was carried out, it was concluded that the mathematical disposition of students with CORE learning models is better than mathematical disposition of students with conventional learning models.